(3YhdeI GdeGds - (3SfZ(B, (3cbGdLjJs; (3QjGV(B, (3MSfs ((3HjQhJ(B:s (3OGQ GdaQGHj(B,s, 2001)
(3GdehGQO GdeGdjI GdTGedI aj GdYGde,GdCReGJ GdeGdjI GdMOjKI aj GdOhd GdfGejI(B:(3JLGQH hOQhS,JOGYjGJ GdSjGSI GdeGdjI hWQb GdJONds
(3GdedGMb(B:(3U(B.253-271s
Keywords: (3GdSjGSI GdeGdjIs; (3GdYhdeIs